Development of Inquiry Model Worksheet for 4th Grader Elementary School Students - Dian Jani Prasinta; M. Thoha B. S. Jaya; Arwin Surbakti (Prodi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi, 2018)
This study aims to develop student worksheets, and to know the effectiveness of thematic based LKS through Inquiry model for fourth grade students of Elementary School I Pinang Jaya. This type of research is research and development (R & D) which refers to Borg & Gall's theory. The population of this research were all fourth grade students of SDN Kemiling Cluster 1 and the samples were 54 students obtained by multistage random samplin technique. Data collection techniques use learning and observation tests. Data analysis technique is done through quantitative analysis for product development that is effectiveness test used N-gain and t test. The results of this study indicate that the developed LKS feasible to be used and effective through experts from material experts and media experts in improving student learning outcomes.